Alcoholism in pregnant women: How their lives are affected in mental health and social life (Research, Society and Development, 2025)
Alcoholism in pregnant women is an important topic to address, considering the history of alcohol and its impacts on the social, emotional and mental health of these women. Alcoholic beverages have been around for millions of years and have been used in many different ways in different cultures. Initially associated with good health and social status, the lack of knowledge about its harmful effects led to its constant consumption over the centuries. However, it was only at the end of the 18th century that alcohol began to be seen as a problem, due to dependence and excessive use. Therefore, the following questions arise here: “How can awareness of the risks of alcoholism during pregnancy be better promoted among health professionals, pregnant women and their families, and how can this awareness contribute to preventing damage to the mental and social health of women and their children?”, “What is the role of educating pregnant women about the risks of alcoholism during pregnancy in preventing alcohol consumption and promoting healthy behaviors during pregnancy?” Seeking to compare with older research and more recent research how this scenario currently stands. The impact of alcohol on pregnant women still needs to be worked on and discussed among health professionals, especially nurses who accompany these women during prenatal care, so that they have control and can bring information to these pregnant women in a welcoming and humanized way.